CSI (Customer Satisfaction Index) and IPA (Importance Performance Analysis) of Speed Rum Harbort in Tidore Island City - Sabaruddin, Sabaruddin; Hakim, Raudha; Tata, Arbain (East Asian Journal of Multidisciplinary Research, 2023)
The city of Tidore Islands is a city whose characteristics are islands, in order to be accessible to other places it has developed itself in the port sector. Where in its development, researchers see the need for community perception as an external basis for determining the development priority scale. This research aims to analyze customer satisfaction and analyze the attributes corrected by Speed ​​Rum Harbor. The sampling method used is accidental sampling and the analysis methods used are Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results showed that Customer satisfaction measurement is 55,51%, it means that customers are quite satisfied. Attributes that need to be improved are of the toilet and waiting room.